SISTEM INFORMASI POSYANDU DESA SALAWANGI KABUPATEN MAJALENGKA BERBASIS WEBSITE - Aprih Widayanto; Yogi Adiyanto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2023)
Posyandu is a basic health activity organized from, by and for the community assisted by health workers. Posyandu is one of the Community-Based Health Efforts (UKBM). So, Posyandu is a self-help activity from the community in the health sector with the person in charge of the village head. The concept of Posyandu is closely related to cohesiveness. The integration referred to includes integration in the aspects of the target, aspects of the location of activities, aspects of the organizing officer, aspects of data and so forth. (MOH RI, 2012: 1). Internet technology can be utilized to gain access to Posyandu information. Data can be stored online so that it can be accessed by the people who are members of the group. A web-based posyandu information system is needed to make this happen. This system is used by Posyandu cadres to record data on posyandu activities. Then it can be accessed by residents to get information about posyandu activities. Internet technology is needed to access information without being bound by place and time. It is hoped that with this web-based Information System, data recording is more easily done by posyandu cadres and information on posyandu activities can be accessed easily by the community. Keywords : Information Systems, Posyandu, Web-Based, Internet